Pengaruh Pemanfaatan Internet, Perpustakaan dan Motivasi Belajar terhadap Hasil Belajar Kearsipan Siswa Kompetensi Keahlian Administrasi Perkantoran SMK Negeri 4 Sijunjung - Ikhwan, Ikhwan (Jurusan PIPS FKIP UMMY Solok, 2019)
This study aims to analyze: 1) Effect of Internet utilization on student motivation. 2) The influence of library utilization on student motivation. 3) Effect of Internet utilization on learning outcomes student. 4) The influence of library utilization on learning outcomes. 5) The influence of learning motivation on learning outcomes. The type of research used is descriptive and associative, with a population of 181 students, the technique of sampling propotional random sampling. The sample of this research is 125 students. Data were collected by questionnaire using Likert scale that has been tested for validity and reliability. Data analysis technique used is Path Analysis (Path Analysis), by using SPSS (Statistical Package For Social Science) program. The result of research are: 1) Internet utilization has significant effect to student's motivation to learn Skill of Office Administration Skill of SMK Negeri 4 Sijunjung. 2) Utilization of the library has a significant effect on the learning outcomes of students Skills Administrative Competence SMK Negeri 4 Sijunjung. 3) Utilization of the internet has a significant effect on Student Motivation Student Skills Competency Skills Administration Office SMK 4 Sijunjung 4) Utilization of libraries have a significant effect on Student Learning Outcomes Competence Skills Office Administration SMK 4 Sijunjung. 5) Learning motivation has a significant effect on Student Learning Outcomes Competence Skills Administration Office SMK 4 Sijunjung